Suggested terms and definitions in photocatalysis and radiocatalysis - N. Serpone; A. V. Emeline (International Journal of Photoenergy)
This document has two principal goals. First, it summarizes some of the issues that pertain to the complexities encountered in photocatalysis. Secondly, it presents suggested terms and definitions proposed to describe those phenomena, which fall under the umbrella of “photocatalysis” and “radiocatalysis”. A distinction is made between the different phenomena that are related to either or both photochemistry and photocatalysis, and to radiation chemistry and radiocatalysis. Consistent definitions of terms in these areas are given. Definitions of important parameters that describe photocatalytic and radiocatalytic phenomena quantitatively are also proposed. As with the related Glossary of Terms in Photochemistry, this document is a dynamic working document to provide the base for lively discussion and debate by the interested community. The terms and definitions will no doubt need to be revisited from time to time as the fields of photocatalysis and radiocatalysis progress and new discoveries reported. Some of the terms used in photochemistry are also given for completion, either verbatim or modified to address the issues of photocatalysis.